2017
DOI: 10.1371/journal.pone.0176601
|View full text |Cite
|
Sign up to set email alerts
|

Persistence and innovation effects in genetic and environmental factors in negative emotionality during infancy: A twin study

Abstract: BackgroundDifficult temperament in infancy is a risk factor for forms of later internalizing and externalizing psychopathology, including depression and anxiety. A better understanding of the roots of difficult temperament requires assessment of its early development with a genetically informative design. The goal of this study was to estimate genetic and environmental contributions to individual differences in infant negative emotionality, their persistence over time and their influences on stability between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 63 publications
(117 reference statements)
0
8
0
Order By: Relevance
“…We identified 5047 publications (4675 publications in databases and 372 publications in references). After duplicate removal and screening, 139 publications were included, containing data on 79 044 twin pairs (31 053 MZ and 47 991 DZ twins), 52 twin cohorts, 21 countries, and 6 continents between 1972 and 2020. The sample included 66 407 twin pairs from Western, educated, industrialized, rich, and democratic countries (in Europe, North America, and Oceania; 84.01%) and 12 637 twin pairs from Africa, Asia, and South America (15.99%) (eResults, eFigures 2 and 3, and eTable 4 in the Supplement).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 5047 publications (4675 publications in databases and 372 publications in references). After duplicate removal and screening, 139 publications were included, containing data on 79 044 twin pairs (31 053 MZ and 47 991 DZ twins), 52 twin cohorts, 21 countries, and 6 continents between 1972 and 2020. The sample included 66 407 twin pairs from Western, educated, industrialized, rich, and democratic countries (in Europe, North America, and Oceania; 84.01%) and 12 637 twin pairs from Africa, Asia, and South America (15.99%) (eResults, eFigures 2 and 3, and eTable 4 in the Supplement).…”
Section: Resultsmentioning
confidence: 99%
“…Quality assessment results are displayed in eFigure 19 in the Supplement. The mean (SD) score for the 106 publications included in the meta-analysis was 75.58% (13.83%).…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has indicated the importance of developmental timing in determining genetic or environmental contributions on the brain and on emotional behaviors (Lacourse et al, 2014; Schumann et al, 2017). At the behavioral level, longitudinal research in twins has shown that that the relative contributions of genetics and environment to aggression and negative affect (behaviors known to be modulated by limbic circuits) are age dependent (Lacourse et al, 2014; Schumann et al, 2017). Longitudinal studies in large twin samples, with repeated brain measures throughout development, may help to further clarify these age‐specific genetic and environmental contributions to brain structure and function.…”
Section: Discussionmentioning
confidence: 99%
“…some new genetic factors emerge in depressive symptoms (Lau and Eley, 2006) or symptoms of anxiety and depression (Nivard et al, 2015) in adolescence. Compared with the 5-month-old baby, the negative emotionality of an 18-month-old baby was affected by persistent and new genetic factors (Schumann et al, 2017). So, it is necessary to use a longitudinal cohort design to investigate the gender differences in the genetic basis of depression at different ages and their developmental changes.…”
Section: Future Directionsmentioning
confidence: 99%